Status of Pradhan Mantri Kisan Samman Nidhi (PM-KISAN) Scheme - Deepak Kumar; Sunil Phougat (Research Developments in Arts and Social Studies Vol. 1, 2022)
Agriculture is the Indian economy's backbone. A large segment of the Indian population is dependent on the agriculture and it allied activities for their livelihood. The Indian government is constantly attempting to improve the agricultural sector by introducing various schemes, one of which is the PM-Kisan Samman Nidhi scheme. It is the government's primary initiative aimed at doubling farmers' income. It stabilises farmers' income, allowing them to use high-yielding variety seeds and modern agricultural technologies that increase agricultural productivity. In the present study, we analyse the PM-Kisan Samman Nidhi scheme implemented in India. We used secondary data gathered from various Indian government reports as well as the PM-Kisan scheme dashboard for this purpose. In the study, descriptive statistical tools such as tables and charts were used. According to the study's findings, PM-Kisan is an ambitious scheme capable of producing significant results. It is a progressive step taken by the Indian government to improve farmers' living conditions. The amount paid to farmers under the PM-Kisan scheme, on the other hand, is insufficient. It is suggested that the amount be sufficient for a decent standard of living.